2022
DOI: 10.3390/ijms23169002
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Vinyl Ketone Activates K+ Efflux to Regulate Stomatal Closure by MRP4-Dependent eATP Accumulation Working Upstream of H2O2 Burst in Arabidopsis

Abstract: Plants regulate stomatal mobility to limit water loss and improve pathogen resistance. Ethyl vinyl ketone (evk) is referred to as a reactive electrophilic substance (RES). In this paper, we found that evk can mediate stomatal closure and that evk-induced stomatal closure by increasing guard cell K+ efflux. To investigate the role of eATP, and H2O2 in evk-regulated K+ efflux, we used Arabidopsis wild-type (WT), mutant lines of mrp4, mrp5, dorn1.3 and rbohd/f. Non-invasive micro-test technology (NMT) data showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Five genes (Glyma.10G017700, Glyma.10G017900, Glyma.10G019000, Glyma.10G019300, and Glyma.10G021800), functionally expressed, showed nonsynonymous missense mutations in exons between the parental lines (Table S6 ): 3 SNPs in Glyma.10G017700 (poly(ADP-ribose) polymerase 2, PARP2), 2 in Glyma.10G021800.1 (degradation of periplasmic proteins 2, DEG2), 1 in each of Glyma.10G017900 (photolyase/blue-light receptor 2, PHR2), Glyma.10G019000 (multidrug resistance-associated protein 4, MRP4) and Glyma.10G019300 (AAA-type ATPase family protein). For only Glyma.10G019000, its Arabidopsis ortholog AT2G27800 has been reported for its function in drought stress (Klein et al 2004 ; Gong et al 2022 ). Compared to SS2-2, we detected multiple variants in the genic region of Glyma.10G019000 in Taekwangkong, including a missense variant in which the amino acid at position 87 changed from Met to Ile and a premature start codon gain variant in 5’ untranslated region (UTR) region (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five genes (Glyma.10G017700, Glyma.10G017900, Glyma.10G019000, Glyma.10G019300, and Glyma.10G021800), functionally expressed, showed nonsynonymous missense mutations in exons between the parental lines (Table S6 ): 3 SNPs in Glyma.10G017700 (poly(ADP-ribose) polymerase 2, PARP2), 2 in Glyma.10G021800.1 (degradation of periplasmic proteins 2, DEG2), 1 in each of Glyma.10G017900 (photolyase/blue-light receptor 2, PHR2), Glyma.10G019000 (multidrug resistance-associated protein 4, MRP4) and Glyma.10G019300 (AAA-type ATPase family protein). For only Glyma.10G019000, its Arabidopsis ortholog AT2G27800 has been reported for its function in drought stress (Klein et al 2004 ; Gong et al 2022 ). Compared to SS2-2, we detected multiple variants in the genic region of Glyma.10G019000 in Taekwangkong, including a missense variant in which the amino acid at position 87 changed from Met to Ile and a premature start codon gain variant in 5’ untranslated region (UTR) region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Glyma.10G019000 is suggested to be an MRP4 which predominantly functions under drought stress in soybean. AT2G47800, an Arabidopsis ortholog of Glyma.10G019000, was highly expressed in stomata and involved in the regulation of stomatal aperture (Klein et al 2004 ; Gong et al 2022 ). Knockout mutants of AtMRP4 showed larger stomatal aperture regardless of light and wilt faster than wild-type under drought conditions (Klein et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoplasmic free Ca 2+ concentrations and H 2 O 2 are thought to play crucial roles in the volatile-sensing mechanisms of plants, although these roles have not been directly demonstrated. We previously showed that evk is recognized by plants and induces H 2 O 2 production, which ultimately mediates stomatal closure to reduce pathogen infection 69 . In the current study, we demonstrated that evk, a volatile compound released by plants, increased the levels of H 2 O 2 and intracellular calcium in Arabidopsis mesophyll cells.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of floral end rot was reduced by increasing the evk content of tomatoes (Solanum lycopersicum) by treating the plants with selenium during the green blossom stage 22 . We previously demonstrated that evk-induced stomatal closure requires MULTIDRUG RESISTANCE-ASSOCIATED PROTEIN 4 (MRP4)-dependent extracellular ATP accumulation and subsequent H 2 O 2 accumulation to regulate K + efflux 23 . Evk is involved in many biological processes, but whether it activates defense genes (e.g., PLANT DEFENSIN 1.2 [PDF1.2] and PATHOGENESIS-RELATED 1 [PR1]) remains unknown.…”
mentioning
confidence: 99%